Poly I:C stimulation in-vitro as a marker for an antiviral response in different cell types generated from Buffalo (Bubalus bubalis). (May 2020) - Vats, Ashutosh; Gautam, Devika; Maharana, Jitendra; Singh Chera, Jatinder; Kumar, Sushil; Rout, Pramod K; Werling, Dirk; De, Sachinandan
Highlights: Buffalo myeloid and non-myeloid cells recognize and respond differently to cytoplasmic delivered poly I:C. Compare to myeloid cell, non-myeloid cell found quicker in detecting poly I:C consequently, robust IFN-β and ISGs expression in fibroblast. High basal level expression of OAS1 and RNaseL in myeloid cells, may inversely influence the IFN-β expression in monocyte and macrophage. HMW poly I:C was better inducer of IFN-β in fibroblast, while LMW was favoured in monocytes and alveolar macrophage. Abstract: The innate immune system is activated upon virus invasion of a host cell by recognizing viral component, such as dsRNA through specific receptors, resulting in the production of type- I IFNs, which confer an antiviral state within the invaded as well as surrounding cells. In the present study, fibroblast, monocyte and macrophage cells derived from water Buffalo ( Bubalus bubalis ) were exposed to a synthetic dsRNA analogue, poly I:C to mimic viral invasion in each cell type. Recognition of poly I:C through cytosolic helicase receptors RIG-I and MDA5 molecule lead to the activation of the RLR pathway, subsequently activating the MAVS-IRF3/7 cascade and the production of antiviral effector molecule like IFNβ and ISGs. Within the different cell types, we identified variability in RLR receptor and IFNβ expression after poly I:C administration. Fibroblasts responded quickly and strongly with IFNβ production, followed by macrophages and monocytes. Despite absolute expression variability among different cell types the expression trend of RLRs pathway genes were similar. Length of poly I:C molecule also influence IFNβ expression in response of RLR pathway. Short (LMW) poly I:C induce stronger IFN-β expression in myeloid (macrophage and monocyte) cells. In contrast long (HMW) poly I:C preferably elicit higher IFNβ expression in non-myeloid (fibroblast) cell. Therefore, MDA5 and RIG-1 plays an indispensable role in eliciting antiviral response in non- immune (fibroblast) host cell. Thus, stimulation of RLR pathway with suitable and potentially cell-type specific agonist molecules successfully elicit antiviral state in the host animal, with fibroblasts conferring a stronger antiviral state compared with the monocytes and macrophages.